Suprascapular Nerve: Is It Important in Cuff Pathology? - Shi, Lewis L. (Hindawi Publishing Corporation, 2012)
Suprascapular nerve and rotator cuff function are intimately connected. The incidence of suprascapular neuropathy has been increasing due to improved understanding of the disease entity and detection methods. The nerve dysfunction often results from a traction injury or compression, and a common cause is increased tension on the nerve from retracted rotator cuff tears. Suprascapular neuropathy should be considered as a diagnosis if patients exhibit posterosuperior shoulder pain, atrophy or weakness of supraspinatus and infraspinatus without rotator cuff tear, or massive rotator cuff with retraction. Magnetic resonance imaging and electromyography studies are indicated to evaluate the rotator cuff and function of the nerve. Fluoroscopically guided injections to the suprascapular notch can also be considered as a diagnostic option. Nonoperative treatment of suprascapular neuropathy can be successful, but in the recent decade there is increasing evidence espousing the success of surgical treatment, in particular arthroscopic suprascapular nerve decompression. There is often reliable improvement in shoulder pain, but muscle atrophy recovery is less predictable. More clinical data are needed to determine the role of rotator cuff repair and nerve decompression in the same setting.